A novel cuproptosis-related lncRNA signature predicts the prognosis and immune landscape in bladder cancer - Bai, Yuchen; Zhang, Qi; Liu, Feng; Quan, Jing (Frontiers in Immunology, 2022)
Background: Bladder cancer (BLCA) was one of the deadliest diseases, with over 550,000 new cases and 170,000 deaths globally every year. Cuproptosis was a copper-triggered programmed cell death and associated with the prognosis and immune response of various cancers. lncRNA could serve as prognostic biomarker and involved in the progression of BLCA. Methods: Gene expression profile of cuproptosis-related lncRNAs were analyzed by using data from The Cancer Genome Atlas. Cox regression analysis and followed least absolute shrinkage and selection operator analysis were performed to construct a cuproptosis-related lncRNA prognostic signature. The predictive performance of this signature was verified by ROC curves and nomogram. We also explored the difference of immune-related activity, tumor mutation burden (TMB), tumor immune dysfunction and exclusion (TIDE), and drug sensitivity between high- and low-risk groups. Results: We successfully constructed a cuproptosis-related lncRNA prognostic signature for BLCA including eight lncRNAs (RNF139-AS1, LINC00996, NR2F2-AS1, AL590428.1, SEC24B-AS1, AC006566.1, UBE2Q1-AS1, and AL021978.1). Multivariate Cox analysis suggested age, clinical stage and risk score were the independent risk factors for predicting prognosis of BLCA. Further analysis revealed that this signature not only had higher diagnostic efficiency compared to other clinical features but also had a good performance in predicting the 1-year, 3-year, and 5-year overall survival rate in BLCA. Notably, BLCA patients with low-risk score seemed to be associated with an inflamed tumor immune microenvironment and had a higher TMB level than those with high rick score. In addition, patients with high-risk score had a higher TIDE score and half maximal inhibitory concentration value of many therapeutic drugs than those with low risk score. Conclusion: We identified a novel cuproptosis-related lncRNA signature which could predict the prognosis and immune landscape of BLCA.